The determinants of the implementation of ad-valorem real property taxation in Poland - Ćwieląg, Krzysztof (Determinanty wdrażania opodatkowania wartości nieruchomości w Polsce, 2012)
Since the middle of the 1990s more and more attention has been paid to the necessity of carrying out a comprehensive reform of the real property taxation system in Poland. The essence of the proposed changes is a departure from the area-related model of property taxation towards a cadastral system in which the amount of tax depends on the value of a real property as determined by a cadastre. The new formula of a real property tax is, first of all, to strengthen and stabilize the finance of local governments. The experience of the majority of countries belonging to the European Union indicate that the reform initiated in Poland is moving in the proper direction – it favours the improvement of the efficiency of the real property taxation system and is consistent with similar solutions functioning in Europe and around the world for many years. The objective of this paper is an attempt to analyze arguments for and against the implementation of ad valorem taxation and a discussion of the fundamental assumptions for the reform, taking into consideration the fiscal and non-fiscal benefits for the finances of the economy of the territorial local government
Nauki i Finansach = Financial Sciences, 2012, Nr 1 (10), s. 32-53
Keywords: territorial local government; communes' revenues; real property taxation system; cadastre; ad valorem property tax; samorząd terytorialny; dochody gmin; system opodatkowania nieruchomości; kataster; podatek katastralny